Frequency of Anxiety and Its Risk Factors Among Working & Non-Working Women of Peshawar - Musa, Nighat; Mehmood, Yasir; Khan, Asghar (Journal of Gandhara Medical and Dental Science, 2018)
OBJECTIVE: to determine the frequency of anxiety & its risk factors among working and non-working women. METHODOLOGY: Study design was descriptive observational. The study duration was seven months (June – December 2016). It was a community based study. Sample size for this study was calculated on 52% prevalence of anxiety Pakistan. A total of 400 women were selected (200 working and 200 non-working women). A semi structured questionnaire was used along with Taylor manifest anxiety scale as study tool. Data was presented in the form of tables and graphs. RESULTS: The frequency of anxiety was 58%. Anxiety was more among working women than non-working women. Most of the women were literate 65.5%. Majority of the women having anxiety were living in nuclear family. The age group most effected was between 21-35 years (67%), 58% were married, single were 34% and 8% were either divorced or widow. Approximately 58% of women with anxiety had less than 2 children and 42% were having more than 2 children. Approximately 88% women with anxiety belonged from low and middle income group having less than 20,000/-PKR and 20,001-50,000/-PKR household income respectively. Only 12% belonged from high group having more than 50,001/- PKR. Conclusions: Anxiety is more common among working women. Married women living in nuclear family system, being single, young age group between 21-35 years, less than 2 children and low household income were the key risk factors.